A Research Framework for Understanding the Practical Impact of Family Involvement in the Juvenile Justice System: The Juvenile Justice Family Involvement Model. Issue 3 (25th September 2015) - Walker, Sarah Cusworth; S. Bishop, Asia; D. Pullmann, Michael; Bauer, Grace
Abstract: Family involvement is recognized as a critical element of service planning for children's mental health, welfare and education. For the juvenile justice system, however, parents' roles in this system are complex due to youths' legal rights, public safety, a process which can legally position parents as plaintiffs, and a historical legacy of blaming parents for youth indiscretions. Three recent national surveys of juvenile justice‐involved parents reveal that the current paradigm elicits feelings of stress, shame and distrust among parents and is likely leading to worse outcomes for youth, families and communities. While research on the impact of family involvement in the justice system is starting to emerge, the field currently has no organizing framework to guide a research agenda, interpret outcomes or translate findings for practitioners. We propose a research framework for family involvement that is informed by a comprehensive review and content analysis of current, published arguments for family involvement in juvenile justice along with a synthesis of family involvement efforts in other child‐serving systems. In this model, family involvement is presented as an ascending, ordinal concept beginning with (1) exclusion, and moving toward climates characterized by (2) information‐giving, (3) information‐eliciting and (4) full, decision‐making partnerships. Specific examples of how courts and facilities might align with these levels are described. Further, the model makes predictions for how involvement will impact outcomes at multiple levels with applications for other child‐serving systems.